Research Note: Oxidative stress and immune response following the administration of live attenuated Mycoplasma gallisepticum vaccination in backyard chicken - Iemmi, T.; Basini, G.; Ramoni, R.; Bussolati, S.; Heredero, A. M. Carrillo; Grasselli, F.; Grolli, S.; Serventi, P.; Bertini, S. (Poultry science, 2023)
In the present study, we investigated a possible relationship between the immune response and the oxidative stress (OS) state trend in a group of 12 chickens after intraocular administration of an attenuated Mycoplasma gallisepticum (MG) vaccine. Blood samples were collected at the vaccination time (T0), after 14 (T1) and 21 d (T2). White blood cell count (WBC), differential leucocyte count, and anti-MG antibodies titer (S/P) were studied as immune response indexes. As plasmatic OS biomarkers levels, we considered malondialdehyde (MDA), nitric oxide (NO), superoxide dismutase (SOD), reactive oxygen metabolites derived compounds (d-ROMs), the ferric reducing ability of plasma (FRAP), and superoxide anion (O2−). After antigenic stimulation, it was observed a significant decrease in monocythemia and a significant increase in thrombocythemia, S/P, MDA, and SOD. Furthermore, subjects with high d-ROMs levels at T0 tended to develop higher cellular mobilization with increases in WBC and lymphocytes accompanied by lower antibody release. It was also observed that the antioxidant components FRAP and SOD were moderately positively correlated to the entity of antibody response.